Aspects of parenting addressed by parenting programmes predict health service usage in childhood and adult hood. (29th September 2015) - Stewart-Brown, S; Arsene, C; Waylen, A; Hutton, J
Abstract : Aim: To estimate the impact of modifiable aspects of parenting on health service usage in childhood and adulthood. Methods: Secondary analysis of data collected in two cohort studies (A) 1000 cases recruited at birth in the Christchurch Health and Development Study in New Zealand and followed up to age 25 years; and (B) 8500 cases recruited at birth to the ALPSAC cohort in Bristol and followed up to age 6 years. Exposures: measures of parenting and parent child relationship; outcomes: measures of attendance at general practitioner (GP) surgeries and hospital in-patient episodes. Poission regression models for GP visits and logistic regression models for hospital admissions. All analyses adjusted for a wide range of confounding factors. Results: (A) In the Christchurch cohort, physical punishment in childhood doubled (CI 1.36 to 4.61) the risk of hospital admission between 21 and 25 years of age in girls and maternal overprotection increased the risk by 4% (CI 1.00 to 1.07). There was no effect in boys. Physical punishment increased the incidence of GP visits by 20% in boys (CI 1.11 to 1.35) and physical punishment (CI 1.03 to 1.12) and sexual abuse (1.05 to 1.13) by 8 and 9%, respectively, in girls. (B) In the ALPSAC cohort, maternal hostility, resentment and confidence, measured at 0–5 years of age increased the risk of GP visits but not hospital admission at age 6 years in univariate analyses. Results of multivariate analyses, currently in progress, will be presented. Conclusion: Aspects of parenting which are modifiable by existing parenting programmes are predictive of health service usage, both in childhood and later in adult life. NHS services to promote parenting are likely to be cost saving to the NHS in both the short and long term.